CP-147 A medication therapy management programme for chronic patient: patient satisfaction in cardiology. (25th February 2017) - Ferreira, V; Hanafia, O; Feyeux, H; Orloff, M; Agullo, M; Collomp, R; Boronad, C
Abstract : Background: The Health System Modernisation law recommends better information and support to patients in their health path. In this context, a medication therapy management programme, AIPAT, was implemented in our hospital. Purpose: The aim of this study was to assess patient satisfaction with this programme. Material and methods: Since March 2015, medication therapy management interventions (MTMi) are offered to outgoing patients from the cardiology department. These interventions, about 15 min and conducted by a pharmacist or specifically trained physician, were structured around two educational tools, designed for this programme:(1) a card game to help patients understand the therapeutic goals of their drugs;(2) a personalised medication schedule, filled in with the patient, listing their treatments with their therapeutic goals and delivered by hand to the patient at the end of the interventions. Finally, a satisfaction survey, completed by the patient, was proposed. Data from this survey were collected and analysed. Results: Over a period of 15 months, 237 MTMi were conducted and 208 satisfaction surveys were returned. Median age of respondent was 77 years. Discharge prescription included a median of 7 drugs. The intervention was found 'useful' or 'essential' in 84% of patients. Almost all patients (99%) were 'satisfied' or 'very satisfied' by messages and information delivered. 79% of patients judged that answers to their questions were satisfying. Most patients (90%) felt they had acquired new knowledge about their pathology and/or their treatments. Regarding the personalised medication schedule, 81% of patients found it 'easy to use', 75% 'essential' and 76% 'adapted to their pathology'. Nearly 9 out of 10 patients declared that they will use this personalised schedule in everyday life. Conclusion: Results showed a very high satisfaction rate and the tools proposed and information provided were very well received by patients. These results highlight the need to continue and extend this programme to other departments and/or hospitals. An assessment of MTMi benefit, particularly for patient compliance, should subsequently be implemented. Finally, electronic transposition of the tools, such as a 'smartphone/tablet' application, could be designed to make them interactive and to enable patients or healthcare providers to update the personalised medication schedule. No conflict of interest